2004
DOI: 10.1152/physiolgenomics.00202.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking neuronal nicotinic acetylcholine receptor β4-subunit and mice lacking both α5- and β4-subunits are highly resistant to nicotine-induced seizures

Abstract: Kedmi, Merav, Arthur L. Beaudet, and Avi Orr-Urtreger. Mice lacking neuronal nicotinic acetylcholine receptor ␤4-subunit and mice lacking both ␣5-and ␤4-subunits are highly resistant to nicotineinduced seizures. Physiol Genomics 17: 221-229, 2004. First published March 2, 2004 10.1152/physiolgenomics.00202.2003.-Nicotine, the main addictive component of tobacco, evokes a wide range of dose-dependent behaviors in rodents, and when administrated in high doses, it can induce clonic-tonic seizures. Nicotine acts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 60 publications
4
73
0
Order By: Relevance
“…Because higher nicotine doses are required, we speculate that different nAChR subtypes are activated (and or desensitized) during WT seizures. Indeed, studies on knock-out mice indicate that other nicotinic subunits (␣3, ␣5, and ␤4) are more important than those containing ␣4 in mediating nicotine seizures in WT (Kedmi et al, 2004;Salas et al, 2004). Although there are no published reports on the nicotineinduced seizure phenotype of ␣4 knock-out mice, we recently found that these mice are similar to their WT littermates in their sensitivity to nicotine seizures (our unpublished data).…”
Section: Nicotine-induced Seizures: Type Sensitivity and Pharmacologymentioning
confidence: 72%
“…Because higher nicotine doses are required, we speculate that different nAChR subtypes are activated (and or desensitized) during WT seizures. Indeed, studies on knock-out mice indicate that other nicotinic subunits (␣3, ␣5, and ␤4) are more important than those containing ␣4 in mediating nicotine seizures in WT (Kedmi et al, 2004;Salas et al, 2004). Although there are no published reports on the nicotineinduced seizure phenotype of ␣4 knock-out mice, we recently found that these mice are similar to their WT littermates in their sensitivity to nicotine seizures (our unpublished data).…”
Section: Nicotine-induced Seizures: Type Sensitivity and Pharmacologymentioning
confidence: 72%
“…␣3 heterozygous and ␣5 null mice have a phenotype similar to that of ␤4 Ϫ/Ϫ mutants in that they are less sensitive to acute nicotine than controls (Salas et al, 2003b(Salas et al, , 2004Kedmi et al, 2004). In addition, the ␣3 and ␣5 subunits are coexpressed with ␤4 in the MHb, the IPN, and peripheral ganglia.…”
Section: Discussionmentioning
confidence: 95%
“…Examples are as follows: the involvement of ␣4 in nicotine-dependent antinociception (Marubio et al, 1999), ␣4, ␤3, and ␤4 in anxiety-related behaviors (Booker et al, 2000;Ross et al, 2000;Salas et al, 2003a), ␤2 in fear conditioning and cocaine-induced nicotine selfadministration (Picciotto et al, 1998), ␣7 in neuronal protection (Laudenbach et al, 2002), and ␣3, ␣5, and ␤4 in nicotineinduced seizures (Salas et al, 2003b(Salas et al, , 2004Kedmi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of thesubunit reduces the high affinity agonist activation of presynaptic nAChRs in the striatum and thalamus without altering their number, and these results indicate that the primary effect of  incorporation is to increase nAChR function without affecting nAChR expression, which may explain why α5 Ko mice are less sensitive to the acute effects of nicotine administration [59,60].…”
Section: Native Nachr Subtypesmentioning
confidence: 92%